Status prawny kobiet w Polsce w świetle ustawodawstwa Unii Europejskiej - Stankiewicz, Wojciech (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The issue of human rights and fundamental liberties in numerous realms of life – whether political and civic, or social and cultural – has been frequently emphasized when discussing the achievements of Western civilization. As a matter of principle, every citizen, regardless of gender, has the same rights, obligations and opportunities in every sphere. This equality implies an equal division of authority and power, that gives women the right to participate in the institutions and public fora that make decisions and issue opinions. This also refers to all other spheres and includes such matters as the right to non-discrimination at work, in business activity, and equal opportunities to obtain material independence. Polish society still does not take sufficient advantage of the opportunities provided by EU instruments. The participation of women in public authorities and public life, the equal status of men and women, equality of rights, or gender-related discrimination are still new ideas, which are both strange and incomprehensible for Polish society. Another problem is posed by harmful stereotypes and false images related to the position of men and women. Poland remains a country where women are responsible for bringing children up, caring for the elderly or the handicapped, household chores, and for material matters pertaining to the family.